2017
DOI: 10.13189/ujps.2017.050402
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol (PEG) Induced Changes in Germination, Seedling Growth and Water Relation Behavior of Wheat (Triticum aestivum L.) Genotypes

Abstract: Pre-sowing seed treated with Polyethylene Glycol (PEG) assumed to be a potential priming agent to increase the germination, seedling growth and water relation behavior of grain. With this view, a lab investigation was carried out to find out the effect of various PEG concentrations on the germination, seedling growth and water relation behavior of wheat. Seeds of ESWYT-5, ESWYT-6 and ESWYT-7 wheat genotypes and BARI Gom 28 were pre-soaked in water with 0%, 5%, 10%, 15% and 20% PEG solutions. Results of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
4
6
0
Order By: Relevance
“…Interestingly, seeds primed with 10% PEG exhibited better seedling growth than other priming treatments, as indicated by higher leaf area and root fresh weight (Table 3). This result was in line with report of Faijunnahar et al (2017) that the best seedling growth was obtained when wheat seed was treated with 10% PEG compared to non-priming, hydropriming, and seedling growth gradually decreased in higher PEG concentrations. The suppression of seedling growth at high PEG concentrations has been reported as due to nutrient imbalance, mobility of toxic ions, and reduction in solubility of applied solutes (Abiri et al, 2016).…”
Section: Seed Priming On Germination and Seedling Growthsupporting
confidence: 92%
“…Interestingly, seeds primed with 10% PEG exhibited better seedling growth than other priming treatments, as indicated by higher leaf area and root fresh weight (Table 3). This result was in line with report of Faijunnahar et al (2017) that the best seedling growth was obtained when wheat seed was treated with 10% PEG compared to non-priming, hydropriming, and seedling growth gradually decreased in higher PEG concentrations. The suppression of seedling growth at high PEG concentrations has been reported as due to nutrient imbalance, mobility of toxic ions, and reduction in solubility of applied solutes (Abiri et al, 2016).…”
Section: Seed Priming On Germination and Seedling Growthsupporting
confidence: 92%
“…Increased root length by osmopriming with PEG was also earlier reported in chickpea (Khadraji et al, 2017). Faijunnahar et al, (2017) concluded that the considerable increase in root length in the primed seeds of wheat might be due to increased metabolic activities in the primed seeds than non-primed.…”
Section: Root Lengthsupporting
confidence: 64%
“…However, germination speed (GS) and mean daily germination (MDG) were significantly improved, especially under suboptimum temperature conditions. Similar to us, Kaur et al, (2002) in chickpea, Farooq et al, (2005) in tomato and Faijunnahar et al, (2017) in wheat have reported improved germination parameters by increasing PEG concentration up to 10% (∼-0.5MPa). A further increase might induce some adverse effects related with decreased water uptake in the osmo priming treatments, especially at water potential lower than -0.5 MPa of PEG (Elkoca et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…It provided significantly higher germination parameters than control and hydro primed seeds, especially under suboptimum temperatures. Similarly, positive effects of PEG osmo priming were previously reported in wheat (Faijunnahar et al, 2017) and sorghum (Zhang et al, 2015). As it is explained, the higher and synchronized germination of primed seeds primarily occurs due to reduction in the lag time of imbibitions, enzyme activation, build-up of germination enhancing metabolites, metabolic repair during imbibition, and osmotic adjustment (Hussain et al, 2016b).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation